Quality of hand-dug wells in selected locations in Lagos coastal aquifer, Nigeria (2010)
Thirty water samples were collected from hand dug wells in Six different locations in the study areas. These include: Ikeja, Lagos Island, Ajah, Victoria Island, Eti- Osa and Yaba. The chloride concentrations of all the samples were acquired and then compared with the World Health Organisation (WHO) standards for chloride content in drinking water. We selected hand dug well because it is a common source of drinking water in the area under consideration. Results show that the average chloride concentrations in all the samples collected in all the six locations are above the WHO value of 250mg/l (value recommended for safe drinking water) with Ajah having the highest Chloride concentration of 606.68mg/l and Ikeja with the least value of 255.37mg/l. This indicates that the water in the considered areas is not safe for drinking. Chloride concentration in the Lagos coastal aquifer may become equal to that at the source at some infinitestimal time and this portends a great danger to the use of groundwater for domestic purposes.